Analisis Maharah Kalam Kurikulum Merdeka Belajar Kampus Merdeka Tingkat MA Kelas 11 Tinjauan CEFR - Rosyada, Amrina; Baroroh, R. Umi (Inovasi: Jurnal Diklat Keagamaan, 2023)
This Research is motivated by the role of the curriculum as a frame of reference for learning Arabic in Indonesia, particulary in the Maharah Kalam (speaking skills). This study aims to examine indicators of attainment skills at MA grade 11 in the Independent Curriculum in terms of the Common Europe Framework of Reference (CEFR) in three aspects, that is: [1] Objectives and characteristics, [2] Learning outcomes and [3] Communicative expressions. This research is a qualitative research with the type of library research. The primary data source for this research is the Merdeka Belajar Curriculum document and the secondary data sources are document that are relevant to this research. The research steps consist of identifying keywords, finding the relevant literatures, evaluating and critically reviewing literature, organizing and writing the result of research. The results of this research are: [1] The KMBKM curriculum is relevant with 2 CEFR competencies (general and communicative) in its objectives, [2] The learning outcomes of the KMBKM curriculum are relevant in themes with CEFR at every level, [3] The communicative expressions in the KMBKM curriculum are appropriate at CEFR levels A1, A2, B1 and B2. This article contributes to providing references in compiling Arabic teaching activities in speaking skills. Keywords: Maharah Kalam, Kurikulum Merdeka Belajar Kampus Merdeka, CEFR